2014
DOI: 10.1073/pnas.1405801111
|View full text |Cite
|
Sign up to set email alerts
|

The role of PI3K/AKT-related PIP5K1α and the discovery of its selective inhibitor for treatment of advanced prostate cancer

Abstract: Significance Prostate cancer is the most common malignancy and the third leading cancer-related cause of death among men of the Western world. Treatment options at advanced stages of the disease are scarce, and better therapies are in urgent need. In our study, we show that the clinically relevant lipid kinase phosphatidylinositol-4-phosphate 5-kinase-α (PIP5Kα) plays an important role in cancer cell invasion and survival by regulating the PI3K/AKT/androgen receptor pathways. Elevated levels of PIP5K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
134
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(140 citation statements)
references
References 41 publications
6
134
0
Order By: Relevance
“…PIP2 is phosphorylated by PI3K to generate PI-3,4,5-P 3 (PIP3), which recruits the serine/threonine kinase AKT to the cell membrane, where it becomes activated, initiating signaling cascades. In this study, Semenas et al (3) find that PIP5K1α is overexpressed in high-grade prostate cancer, and its expression correlates with PIP2 and AR expression in these tissues. The authors further demonstrate that PIP5K1α contributed to malignant transformation in prostate cancer cell lines through increased invasion, enhanced stability or expression of AR, and expression of cellular proliferation markers such as cyclin-dependent kinase 1 (CDK1).…”
supporting
confidence: 50%
“…PIP2 is phosphorylated by PI3K to generate PI-3,4,5-P 3 (PIP3), which recruits the serine/threonine kinase AKT to the cell membrane, where it becomes activated, initiating signaling cascades. In this study, Semenas et al (3) find that PIP5K1α is overexpressed in high-grade prostate cancer, and its expression correlates with PIP2 and AR expression in these tissues. The authors further demonstrate that PIP5K1α contributed to malignant transformation in prostate cancer cell lines through increased invasion, enhanced stability or expression of AR, and expression of cellular proliferation markers such as cyclin-dependent kinase 1 (CDK1).…”
supporting
confidence: 50%
“…Our results demonstrated that EPA decreased cancer proliferation more efficiently compared with DHA, suggesting a possible treatment for metastatic castration-resistant prostate cancer. In addition, PC3 cells expressed phosphoinositide 3 kinase (PI3K)/AKT-related PIP5K1α (15), and HBx transfection in HepG2 cells led to the expression of nuclear factor (NF)-κβ (16). NF-κβ is downstream of PI3K/AKT and is a transcription factor that acts on a variety of genes.…”
Section: Discussionmentioning
confidence: 99%
“…PI3K, PKC and PLC) that are altered in tumours and in inflammatory as well as in autoimmune diseases. One selective PIP5Ka inhibitor has recently been identified and proved effective in inhibiting advanced prostate cancer progression [166] and T lymphocyte activation (L. Tuosto, personal communication). Thus, more extensive investigation of the mechanisms regulating PIP5K recruitment, activation and regulation by its interacting partners may prove useful for the design of more selective targeted therapies for immune-based diseases.…”
Section: Discussionmentioning
confidence: 99%